2012
DOI: 10.1074/jbc.m111.276618
|View full text |Cite
|
Sign up to set email alerts
|

Novel Regulation of Fibroblast Growth Factor 2 (FGF2)-mediated Cell Growth by Polysialic Acid

Abstract: Background: Polysialic acid (polySia) binds neurological factors, BDNF and dopamine. Results: PolySia specifically binds FGF2 and inhibits the cell growth facilitated by signaling through a ternary complex of FGF2, FGFR, and heparan sulfate (HS). Conclusion: PolySia regulates the FGF2-mediated cell growth differently from HS. Significance: A new function of polySia to regulate the action of neurological factors is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 49 publications
(115 reference statements)
1
68
0
Order By: Relevance
“…However, as highlighted for FGF2 bound to heparan sulfate and polySia, the type of carbohydrate chain will determine how a soluble factor is displayed (72).…”
Section: Discussionmentioning
confidence: 99%
“…However, as highlighted for FGF2 bound to heparan sulfate and polySia, the type of carbohydrate chain will determine how a soluble factor is displayed (72).…”
Section: Discussionmentioning
confidence: 99%
“…-Recently, we demonstrated that polySia binds neurobiologically active molecules, such as BDNF, FGF2, and neurotransmitters (8,9,11). Here, we first attempted to confirm if polySia on microglia also captures BDNF.…”
Section: Polysia Captures Bdnf Which Is Released Via Degradation Of mentioning
confidence: 99%
“…The unique polySia glycotope has been considered to inhibit cellcell interactions through its anti-adhesive effects (7). Recently, polySia also functions as a reservoir for neurobiologically active molecules such as BDNF, FGF2, and neurotransmitters (8,9), regulating their availability and concentrations in the brain. In addition, relationships between altered polySia and schizophrenia have been reported (10 -12).…”
mentioning
confidence: 99%
“…Conversely, decreased expression of polysialylated NCAM is associated with certain neuropsychiatric disorders, including schizophrenia (14). Studies by Sato, Kitajima, and colleagues (15)(16)(17) suggest why this might be the case. They were the first to demonstrate that polySia binds neurotrophic factors, neurotransmitters, and growth factors, and their work suggests that the presence of polySia can modulate signaling by these molecules.…”
mentioning
confidence: 99%